2015
DOI: 10.1016/j.jfa.2015.04.014
|View full text |Cite
|
Sign up to set email alerts
|

Non-extremal sextic moment problems

Abstract: Positive semidefiniteness, recursiveness, and the variety condition of a moment matrix are necessary and sufficient conditions to solve the quadratic and quartic moment problems. Also, positive semidefiniteness, combined with another necessary condition, consistency, is a sufficient condition in the case of extremal moment problems, i.e., when the rank of the moment matrix (denoted by r) and the cardinality of the associated algebraic variety (denoted by v) are equal. However, these conditions are not sufficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…Therefore, only the cases m = 1, 2, 3 and 4 (the quadratic, the cubic and the quartic moment problem) have been completely achieved. All the other cases (quintic, sixtic, ...) are open and interest several authors; as indicated in many recent papers (see, for instance, [13,15,16,37,38]).…”
Section: Introductionmentioning
confidence: 97%
“…Therefore, only the cases m = 1, 2, 3 and 4 (the quadratic, the cubic and the quartic moment problem) have been completely achieved. All the other cases (quintic, sixtic, ...) are open and interest several authors; as indicated in many recent papers (see, for instance, [13,15,16,37,38]).…”
Section: Introductionmentioning
confidence: 97%
“…So it remains to study the case y 2 = 1 or equivalently the TMP on the union of two parallel lines (TMP-2pl). Concerning the TMP on the varieties beyond the quadratic ones the solutions typically require testing some additional numerical conditions which depend on given moments (see [CY14,CY15,Yoo17a,Yoo17b]).…”
Section: Introductionmentioning
confidence: 99%
“…Using the flat extension theorem as the main tool the 2-dimensional TMP has been concretely solved in the following cases: K is the variety defined by a polynomial p(x, y) = 0 Fia11], M(k) has a special feature called recursive determinateness [CF13] and in the extremal case with the equality in the variety condition [CFM08]. Some other special cases have been solved in [Kim14, CS15,Fia17,Ble15,BF20]. In [Fia11], Fialkow studied also the TMP for the curves of the form y = g(x) and yg(x) = 1, where g ∈ R[x] is a polynomial, and obtained the bound on the degree m for which the existence of a positive extension M(m) of M(k) is equivalent to the existence of a measure.…”
Section: Introductionmentioning
confidence: 99%